Tri-Band Rectenna Dedicated to UHF RFID, GSM-1800 and UMTS-2100 Frequency Bands - Ognadon Assogba; Abdoul Karim Mbodji; Arnaud Bréard; Abdou Karim Diallo; Yvan Duroc (Sensors, 2022)
The omnipresence of connected objects leads to the quasi-permanent presence of electromagnetic waves from different sources in our environment. This article presents a new electromagnetic energy harvesting device, rectenna type, which offers the advantage of being versatile. Indeed, the proposed prototype is compatible with three frequency bands of radio standards widely deployed today (UHF RFID, GSM-1800, and UMTS-2100), and its performances remain good for low to very low ambient power levels as well as for different loads depending on the targeted application. The proposed solution is based on a tri-band antenna with very good efficiency and a bandwidth of at least 80 MHz for each of the operating frequencies. Moreover, the associated rectifier circuit is also tri-band and offers good performance in terms of RF-to-DC conversion efficiency for input levels varying in a rather wide range of power levels. The study is based on a design phase by simulation until the realization of prototypes and their experimental characterization. The designed rectenna is compared with solutions found in the literature.